3D pore structure, thermal and physical properties of metakaolin-black rice husk ash-based alkali-activated cement. Issue 4 (4th July 2022) - Wongkeo, Watcharapong; Torkittikul, Pincha; Nochaiya, Thanongsak; Pakawanit, Phakkhananan
Abstract : Alkali-activated cement (AAC) produced with metakaolin and black rice husk ash was investigated. The characteristics, physical properties, and thermal properties were investigated. Porosity assessments were carried out using synchrotron radiation X-ray tomographic microscopy (XTM). The results revealed that the concentration of NaOH solution and Na2 SiO3 solution was the key parameter which affected the morphology and properties of AAC. Particle-structures and prolonged structures were formed when using NaOH as an activator. However, stacked plate-like structures were observed when using Na2 SiO3 together with NaOH. The amorphous phases of N-A-S-H gel and geopolymer were formed. XTM profiles showed that the pore volume decreased with increasing NaOH solution concentration and Na2 SiO3 contents. The 3D images illustrated that the pore structures were occupied by pores less than 50 µm in size. Pore connections within the range of 0–50 µm were the main parameter which controlled the thermal and physical properties.